ПОМОГИТЕ ПОЖАЛУЙСТО!
Упростите выражение:
3 умножить(а-б)во второй степени-3б во второй степени

2
3*(а-b)(в квадрате)-3b(в квадрате)=3*(a(в квадрате)-2ab+b(в квадрате))-9b(в квадрате)= 3a(в квадрате) - 6ab+3b(в квадрате) - 9b(в квадрате)= 3a(в квадрате)-6b(в квадрате) -6ab
спасибо огромное)
пожалуйста)
как вот это решить?как вот это решить 3 умножить(4+с)умножить(3-4с)

Ответы и объяснения

  • Etim
  • хорошист
2013-09-14T12:50:40+00:00
  • Участник Знаний
2013-09-14T12:50:40+00:00
3 * (A - B)^2 - 3B^2 = 3*( A^2 - 2AB + B^2) - 3B^2 = 3A^2 - 6AB + 3B^2 - 3B^2 =
= 3A^2 - 6AB = 3A*(A - 2B)